Studio Ghibli: Counter IP perspective on visual styles generated by AI image generators - Darmawan, Andreas James; Jeong, Min-Sook; Kim, Hye-Kyung (Jurnal Desain, 2025)
This study quantitatively analyzes how the use of AI Image Generators to replicate Studio Ghibli’s visual style is perceived in public and academic discourse, particularly concerning legal, ethical, and cultural dimensions. Employing a quantitative content analysis using NVivo-assisted coding of secondary data gathered from 20 scholarly and professional publications between 2020 and 2025, the research investigates the evolving relationship between human creativity and generative technology. The results indicate that the majority of sources (60%) interpret AI’s role in the Ghibli context as a non-commercial form of transformative fair use that serves as a medium of Japanese cultural promotion, whereas 30% regard it as a potential copyright infringement, and 10% emphasize the need for new ethical regulation. The findings reveal the ambivalence of AI as both a challenge to human authorship and a catalyst for collaborative innovation that redefines aesthetic expression through algorithmic creativity. The phenomenon of Ghibli-style AI art also contributes to Japan’s cultural soft power, reinforcing its humanistic and ecological aesthetic values within the global digital sphere. The study concludes that conventional copyright frameworks are insufficient to regulate hybrid authorship involving humans and machines, necessitating new policies grounded in fairness, transparency, and moral responsibility. Furthermore, the study offers pedagogical and industrial implications, highlighting the importance of integrating AI ethics and intellectual property literacy into art education and creative practices to ensure a responsible and inclusive generative art future.